2008
DOI: 10.1007/s00421-008-0865-9
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil response of anaerobic jump trained diabetic rats

Abstract: This paper investigated the effect of jump training on blood biochemical parameters and neutrophil responses of diabetic rats. Male Wistar rats were divided into control, trained, diabetic and trained-diabetic groups. Diabetes was induced by i.v. injection of streptozotocin. Jump training consisted of six sets of ten jumps in water with overload of 50% of body mass with 1-min of resting, four times per week during 6 weeks. Plasma glucose, lactate, triacylglycerol and total cholesterol concentrations, different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…These animals exhibit many changes similar to those seen in humans with type 1 DM, such as hyperglycemia, dyslipidemia, and weight loss (8). We investigate here the effect of interval training, using low-volume and highintensity exercise, on blood biochemical and immune parameters in type 1 diabetic rats.…”
mentioning
confidence: 99%
“…These animals exhibit many changes similar to those seen in humans with type 1 DM, such as hyperglycemia, dyslipidemia, and weight loss (8). We investigate here the effect of interval training, using low-volume and highintensity exercise, on blood biochemical and immune parameters in type 1 diabetic rats.…”
mentioning
confidence: 99%
“…Concerning the anaerobic training protocols, many studies have used efforts with jumps performed in water 3,4 and on platform through eletric stimulation 5,6 in different nutritional 7 and pathological conditions 3 . The training protocols with jumps are composed of 3-4 sets of 10-12 jumps with intervals of 60-90s 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…The training protocols with jumps are composed of 3-4 sets of 10-12 jumps with intervals of 60-90s 6,7 . Additionally, the intensity increase is performed with weight addition corresponding to the body weight 4 or a maximum repetition 8 . High-intensity physical training performed for short periods of time has significant effects on the anaerobic glycolytic system, in a way that the increase of the ATP production is followed by increase of muscular lactate production 9 .…”
Section: Introductionmentioning
confidence: 99%
“…These animals exhibit many changes similar to those seen in humans with DM, such as hyperglycemia and dyslipidemia 10 . Our group have previously shown that, after six weeks of IT, STZ-induced diabetic rats present a significant reduction of glycaemia 11 .…”
Section: Introductionmentioning
confidence: 84%